The physics of solar cells : perovskites, organics, and photovoltaic fundamentals - Bisquert, Juan (CRC Press, 2018)
"Energy devices with solar cells and batteries are crucial in the drive to obtain a carbon-free energy economy. Funding and commercial applications are focused on developing new materials and devices that perform required energy conversion and storage processes with high efficiency, adequate capabilities, and low production costs. This book provides an accessible summary and introduction of the main physicochemical principles that govern solar cells, perovskites, and organic materials. Recent rapid advances in the science and technology of solar cells with the discovery of perovskite solar cells and their development to a highly efficient semiconductor solar cell are highlighted"--